ESTABLISHMENT OF HISTORICAL EDUCATION AND SCIENCE IN THE STAVROPOL STATE PEDAGOGICAL INSTITUTE IN THE 1940-1960s - Vladimir Nozdrinov (Гуманитарные и юридические исследования)
The article studies the establishment of historical science and education in Stavropol in the context of time and attempts to assess the activities of first professional historians of Stavropol by the example of professors V. A. Romanovsky and P. A. Shatsky. The author studied the conditions and the peculiarities of scientific historical school development in the Stavropol Pedagogical Institute. The analysis of the state of historical knowledge in the first half of the 20th century is conducted, namely, the absence of academic centers to study the history of the North Caucasus and the Stavropol region and train scientific personnel. The article studies the reasons for the establishment of the historical faculty in the postwar period and the context of inviting a well-known all-Union level scientist Viktor Romanovsky that was fallen in disgrace that time. It is claimed that prior to V. A. Romanovsky the historical knowledge in the Stavropol region was at the prescientific level. The author differentiates the concepts of local history and historical science. The region needed to establish its own database of historical studies while seriously exploring the North Caucasus region and training its history experts - not only school teachers but also university-level scientists who were supposed to study the history of the North Caucasus. The author views the first period of establishing the Faculty of History (1946 - the end of the 1960s) as a fruitful stage in the development of Stavropol historical school. The works of the 50s-60s of the XX century served the basis for further study of many problems of political, economic, social and cultural development of the North Caucasus.